Polishing pad for polishing silicon substrate and production process thereof
By using polyester fiber and viscose fiber nonwoven fabrics of a specific proportion in the silicon substrate polishing pad, and combining polyurethane and hygroscopic penetrants with different elastic modulus, the scratching and grinding problem caused by impurity accumulation during the polishing process is solved, achieving more efficient polishing and longer service life.
Patent Information
- Application Number
- CN202510235605.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-06-17
AI Technical Summary
The existing silicon substrate polishing pads are prone to produce fine particle impurities during the polishing process, resulting in the scratching and grinding of silicon substrates. Especially on small soft silicon substrates with high precision requirements, it is prone to scratching and excessive wear.
A non-woven fabric composed of polyester fiber and viscose fiber in a specific proportion is used, and two polyurethanes with different elastic modulus are combined to form a polyurethane impregnated structure, and a hygroscopic penetrant is added to improve the flexibility, adsorption and overall performance of the polishing pad.
It significantly reduces the possibility of scratching and excessive wear of silicon substrates during polishing, improves polishing efficiency and product qualification rate, and extends the service life of the polishing pad.
Smart Images

Figure BDA0005292660510000051 
Figure BDA0005292660510000052 
Figure BDA0005292660510000091
Abstract
Description
Technical Field
[0001] This application relates to the technical field of silicon substrate polishing, and particularly to a polishing pad for silicon substrate polishing and a preparation method thereof. Background Art
[0002] As a key semiconductor material, silicon substrates play a crucial role in modern electronics industry. With the rapid development of integrated circuit technology, the requirements for the surface quality of silicon substrates are increasing day by day. In particular, its planarization degree directly affects the success rate and performance of chip manufacturing. In this context, the polishing process has become one of the core links to achieve high-precision processing of silicon substrates. As the core component in the polishing process, the performance of the polishing pad directly determines the quality and yield of the final product.
[0003] Currently, for the polishing operation of silicon substrates, traditional polishing pads are usually formed by impregnating non-woven fabrics made of synthetic fibers such as polyester fibers and nylon fibers with glue. Such polishing pads mainly rely on single materials or simple formulations to meet basic requirements. Specific implementation methods include, but are not limited to: using high-strength polyester fibers to construct a support framework to enhance wear resistance; improving lubrication characteristics by introducing nylon fibers; and adding a specific proportion of rubber-like substances to enhance the flexible adaptability.
[0004] However, although the above conventional means can improve the wear resistance of the polishing pad, fine particle impurities will be generated during the polishing process. As the polishing time goes by, more and more impurities accumulate on the surface, which is likely to cause scratching of the silicon substrate. Especially when facing small soft silicon substrates with extremely high precision requirements, it is extremely easy to cause scratching due to local pressure concentration, thereby reducing the qualification rate of the silicon substrate. Summary of the Invention
[0005] In order to avoid the scratching phenomenon of silicon substrates during the production process, a polishing pad for silicon substrate polishing and a preparation method thereof are provided.
[0006] In the first aspect, this application provides a polishing pad for silicon substrate polishing, including a non-woven fabric and a polyurethane impregnated structure. The impregnated layer is formed by impregnating the non-woven fabric with polyurethane glue solution and curing. The non-woven fabric is produced by needling 25 - 35 wt% of polyester fibers and 65 - 75 wt% of viscose fibers; the polyurethane glue solution includes: 50 - 60 parts by weight of polyurethane with an elastic modulus of 38 - 45 MPa, 40 - 50 parts by weight of polyurethane with an elastic modulus of 60 - 70 MPa, and 140 - 160 parts by weight of solvent.
[0007] By adopting the above technical solution, the non-woven fabric of the polishing pad is compounded by polyester fiber and viscose fiber in a specific proportion, which combines softness, wear resistance and adsorption. It can quickly remove the stains and debris generated during the polishing process, ensure the full play of the polishing agent, improve the polishing efficiency and effectively protect the surface of the silicon substrate from scratching or excessive wear. In addition, by compounding two polyurethanes with different elastic moduli, the flexibility and comprehensive performance of the polishing pad are further enhanced, so that the possibility of scratching and excessive wear can be significantly reduced during the silicon substrate polishing process.
[0008] In summary, the present application uses two polyurethanes with different elastic moduli for compounding to play a role in increasing flexibility, and cooperates with the non-woven fabric made of polyester fiber and viscose fiber to further improve the flexibility, adsorption, etc. of the polishing pad, reduce the wear of the silicon substrate, and reduce the possibility of particle stains and the like generated during the polishing process accumulating on the surface of the polishing pad, resulting in scratching of the surface of the silicon substrate, etc., so as to ensure the durability of the polishing pad.
[0009] Preferably, the solvent is DMF.
[0010] DMF is N,N-dimethylformamide. The selection of DMF as the solvent makes the polyurethane glue solution have good solubility and uniformity, which helps to improve the penetration effect during the dipping process, and thus improves the overall performance of the polishing pad. At the same time, DMF has good water solubility. When the polyurethane glue solution in the non-woven fabric contacts water, the polyurethane is easily precipitated and cured, while DMF is easily dispersed in water. It should be noted that the polyurethane in the present application is a solid polyurethane resin, which is a polymer material with excellent mechanical properties formed by the polycondensation reaction of polyol and polyisocyanate.
[0011] Preferably, the fiber specifications of both the polyester fiber and the viscose fiber are 30-50D / 45-60mm.
[0012] By adopting the above technical solution, the fiber specifications of the polyester fiber and the viscose fiber are limited to 30-50D / 45-60mm. The fibers within this size range can provide better softness and adsorption while ensuring the mechanical strength of the non-woven fabric, which is beneficial to effectively capture debris during the polishing process and reduce damage to the surface of the silicon substrate. 3-5D is the fineness, and 45-60mm is the fiber length.
[0013] Preferably, the polyurethane glue solution further includes 1-3.5 parts by weight of a moisture absorption penetrant.
[0014] By adopting the above technical solution, the addition of the moisture absorption and penetration agent can significantly improve the bonding strength between the polyurethane adhesive and the non-woven fabric, making the non-woven fabric stick together more firmly, thereby enhancing the overall structural stability of the polishing pad. At the same time, the moisture absorption and penetration agent also has excellent moisture absorption performance, which can maintain the appropriate humidity of the polishing pad and avoid damage to the silicon substrate caused by drying. In addition, the components in the moisture absorption and penetration agent interact synergistically, further improving the flexibility and wear resistance of the polishing pad, ensuring effective adsorption and removal of fine impurities during the polishing process, reducing the risk of scratching the surface of the silicon substrate, and prolonging the service life of the polishing pad.
[0015] Preferably, the moisture absorption and penetration agent is prepared from the following raw materials by weight percentage: Methyl vinyl ether-maleic anhydride copolymer 10-30% (Acryloxymethyl)dimethylmethoxysilane 5-10% Maleic anhydride amino alcohol acrylate 2-8% Carboxyl polycaprolactone 2-10% Initiator 1-2% The balance is active diluent.
[0016] By adopting the above technical solution, the methyl vinyl ether-maleic anhydride copolymer in the moisture absorption and penetration agent significantly improves the bonding strength between the polyurethane adhesive and the non-woven fabric, enhances the strength and heat resistance of the non-woven fabric, and makes it more suitable for harsh environments such as high temperature and humidity. At the same time, (acryloxymethyl)dimethylmethoxysilane further increases the flexibility and wear resistance of the material, promotes the uniform penetration of the polyurethane adhesive in the non-woven fabric, avoids the formation of a waterproof film, and ensures effective coating of the fiber surface.
[0017] Maleic anhydride amino alcohol acrylate endows the material with good water absorption performance, improves the overall adsorption capacity and stable humidity during the polishing process, and acts together with the viscose fiber in the non-woven fabric to promote the absorption of its stains and impurities, and improve the surface self-cleaning property of the polishing pad. Carboxyl polycaprolactone synergistically optimizes the flexibility and durability of the material with other components, helps to efficiently remove fine impurities generated during the polishing process, and prevents them from scratching or contaminating the silicon substrate. The initiator ensures the full reaction between the components, and the active diluent adjusts the fluidity of the system, jointly ensuring the best performance of the moisture absorption and penetration agent.
[0018] Preferably, the active diluent is acrylate-based polyethylene glycol.
[0019] By adopting the above technical solution, the active diluent is selected as acrylate-based polyethylene glycol, which can effectively improve the dispersibility and fluidity of the moisture absorption penetrant, making it easier for the moisture absorption penetrant to be evenly distributed in the polyurethane adhesive. This not only enhances the bonding force between the polyurethane adhesive and the non-woven fabric, but also improves the overall performance of the polishing pad, including flexibility, wear resistance and adsorption. In addition, the presence of acrylate-based polyethylene glycol helps to maintain the appropriate humidity of the polishing pad, further reducing the risk of scratching on the surface of the silicon substrate during the polishing process.
[0020] Preferably, the moisture absorption penetrant is prepared by the following method: Weigh methyl vinyl ether-maleic anhydride copolymer, (acryloxymethyl)dimethylmethoxysilane, maleic anhydride amino alcohol acrylate, carboxyl polycaprolactone, active diluent, initiator according to weight percentage, mix them evenly, and heat react to obtain the moisture absorption penetrant.
[0021] By adopting the above technical solution, the moisture absorption penetrant is prepared from methyl vinyl ether-maleic anhydride copolymer, (acryloxymethyl)dimethylmethoxysilane, maleic anhydride amino alcohol acrylate, carboxyl polycaprolactone, active diluent. This moisture absorption penetrant can significantly improve the flexibility and wear resistance of the polishing pad, while enhancing its adsorption performance, effectively capturing the tiny impurities generated during the polishing process, and avoiding scratching or contamination of the surface of the silicon substrate. In addition, the moisture absorption penetrant also improves the bonding force between the polyurethane adhesive and the non-woven fabric, improves the stability and durability of the overall structure, and ensures that the polishing pad still maintains excellent performance under complex working conditions.
[0022] In the second aspect, a preparation method of a polishing pad for polishing a silicon substrate includes the following steps: Polyurethane adhesive: Weigh polyurethane with an elastic modulus of 38-45 MPa, polyurethane with an elastic modulus of 60-70 MPa, and solvent according to weight percentage, mix them evenly to obtain the polyurethane adhesive; Non-woven fabric: Weigh polyester fiber and viscose fiber according to weight percentage, mix them evenly, and then transfer them to a needling device for needling to obtain the non-woven fabric; Impregnation: Perform impregnation treatment on the non-woven fabric to obtain semi-finished product A; Solidification: Put semi-finished product A into a solidification tank for solidification treatment, then perform water washing treatment and drying to obtain the polishing pad.
[0023] By adopting the above technical solution, the prepared polishing pad has excellent comprehensive performance. The specific effects are as follows: The non-woven fabric produced by the needle punching process after the polyester fiber and viscose fiber are compounded in a specific proportion has both softness, wear resistance and adsorption, and can quickly remove the stains and debris generated during the polishing process, ensuring that the polishing liquid can fully play its role, improving the polishing efficiency, and at the same time effectively protecting the surface of the silicon substrate from scratches or excessive wear.
[0024] The impregnated layer formed by compounding two kinds of polyurethanes with elastic moduli of 38 - 45 MPa and 60 - 70 MPa respectively significantly enhances the flexibility and durability of the polishing pad, further improves its adaptability during the polishing process of the silicon substrate, and reduces the possibility of scratches and excessive wear.
[0025] The introduction of the moisture absorption and penetration agent not only promotes the effective penetration of the polyurethane adhesive into the non-woven fabric, but also improves the overall softness, wear resistance and water absorption of the polishing pad, while strengthening the adhesion between the fibers and optimizing the working stability and service life of the polishing pad.
[0026] Preferably, the impregnation time is 1 - 2 min; the solidification treatment time is 50 - 70 min; the drying time is 15 - 25 min, and the drying temperature is 145 - 155 °C.
[0027] By adopting the above technical solution, controlling the impregnation time within the range of 1 - 2 minutes can enable the polyurethane adhesive to fully penetrate into the non-woven fabric without causing excessive waste, ensuring that the polishing pad has good structural stability and uniformity; setting the solidification treatment time to 50 - 70 minutes helps the polishing pad to form stable physical properties and appropriate hardness, improving durability; setting the drying time to 15 - 25 minutes and carrying out at 145 - 155 °C can not only effectively remove moisture, but also avoid the damage of high temperature to the material properties, thus maintaining the excellent quality of the polishing pad. The selection of these parameters works together to improve the consistency and controllability of the preparation process, and further enhance the reliability and applicability of the final product.
[0028] Preferably, the polyurethane adhesive also includes 0.2 - 3.5 parts by weight of the moisture absorption and penetration agent.
[0029] By adopting the above technical solution, the addition of the moisture absorption and penetration agent can significantly improve the overall performance of the polishing pad. Specifically, the components in the moisture absorption and penetration agent act synergistically to enhance the bonding force between the polyurethane adhesive and the non-woven fabric, making the non-woven fabric adhere together more firmly, thereby improving the service life and stability of the polishing pad. At the same time, the moisture absorption and penetration agent also improves the flexibility and wear resistance of the polishing pad, avoiding damage to the surface of the silicon substrate due to being too hard or too brittle during the polishing process. In addition, the moisture absorption and penetration agent has good moisture absorption properties, can maintain the appropriate humidity of the polishing pad, reduce the risk of damage to the silicon substrate, and promote the effective adsorption of fine polishing impurities by the viscose fiber, preventing frictional damage caused by impurity accumulation.
[0030] In summary, the present application includes at least one of the following beneficial technical effects: 1. Through the reasonable compounding of polyester fiber and viscose fiber, the polishing pad has both softness and wear resistance, can effectively protect the surface of the silicon substrate, avoid scratching or excessive wear, and at the same time quickly adsorb stains and debris generated during the polishing process, ensure the full action of the polishing agent, thereby improving the polishing efficiency; 2. Two polyurethanes with different elastic moduli are compounded and then impregnated with glue on the non-woven fabric, enhancing the overall flexibility and comprehensive performance of the polishing pad, and significantly reducing the risk of scratching and the possibility of excessive wear of the silicon substrate during the polishing process; 3. The addition of the moisture absorption and penetration agent not only improves the bonding force between the polyurethane adhesive and the non-woven fabric, but also optimizes the water absorption and wear resistance of the polishing pad, ensures its stable operation under complex working conditions, and extends the service life. Detailed implementation mode
[0031] The following further elaborates on the present application in conjunction with examples.
[0032] Partial raw materials: The polyurethane of the present application is Covestro solvent-based polyurethane Polyurethanes with an elastic modulus of 40 MPa and an elastic modulus of 60 MPa in XP; (Acryloyloxymethyl)dimethylmethoxysilane has the following molecular structure: Maleic anhydride amino alcohol acrylate has the following molecular structure: The structural formula of carboxyl polycaprolactone (PCL-COOH) can be expressed as: [CH2-CH2-CH2-CH2-CH2-COO]n, where n represents the degree of polymerization, and n is 10 - 15; Methyl vinyl ether-maleic anhydride copolymer CAS No. 9011-16-9.
[0033] Preparation example of wetting agent Preparation Example 1 The wetting penetrant is prepared from raw materials in the following weight percentages: By weight percentage, 20% of methyl vinyl ether - maleic anhydride copolymer, 15% of (acryloxymethyl) dimethyl methoxysilane, 18% of maleic anhydride amino alcohol acrylate, 10% of carboxyl polycaprolactone, 2% of initiator, and 35% of active diluent are weighed and mixed, heated to 65 °C, and reacted for 155 min to obtain the moisture-absorbing penetrant. The initiator is benzoyl peroxide; the active diluent is polyethylene glycol (200) diacrylate.
[0034] Preparation Examples 2 - 3 The differences between Preparation Examples 2 - 3 and Preparation Example 1 are as follows: the dosages of the raw materials are different, as specifically shown in Table 1; Table 1 Dosages of raw materials in Preparation Examples 1 - 3 (%) Raw materials Preparation Example 1 Preparation Example 2 Preparation Example 3 Methyl vinyl ether - maleic anhydride copolymer 20 30 35 (Acryloxymethyl)dimethylmethoxysilane 15 20 23 Maleic anhydride amino alcohol acrylate 18 15 10 Carboxyl polycaprolactone 10 6 2 Initiator 2 1 1 Reactive diluent 35 28 29 Preparation of Comparative Examples Preparation of Comparative Example 1 The difference between Preparation of Comparative Example 1 and Preparation Example 1 is that the methyl vinyl ether - maleic anhydride copolymer is equally replaced by carboxyl polycaprolactone.
[0035] Preparation of Comparative Example 2 The difference between Preparation of Comparative Example 2 and Preparation Example 1 is that the carboxyl polycaprolactone is equally replaced by methyl vinyl ether - maleic anhydride copolymer.
[0036] Preparation of Comparative Example 3 The difference between Preparation of Comparative Example 3 and Preparation Example 1 is that the maleic anhydride amino alcohol acrylate is equally replaced by (acryloxymethyl) dimethyl methoxysilane.
[0037] Preparation of Comparative Example 4 The difference between Preparation of Comparative Example 4 and Preparation Example 1 is that the (acryloxymethyl) dimethyl methoxysilane is equally replaced by maleic anhydride amino alcohol acrylate. Examples
[0038] Example 1 A polishing pad for polishing a silicon substrate is prepared by the following method: Polyurethane solution: By weight, 55 parts of polyurethane with an elastic modulus of 40 MPa, 45 parts of polyurethane with an elastic modulus of 65 MPa, and 150 parts of solvent are weighed and mixed evenly to obtain the polyurethane solution; Non-woven fabric: By weight percentage, 30% of polyester fibers and 70% of viscose fibers are weighed and mixed evenly, and then transferred to a needling device for needling to obtain the non-woven fabric; Impregnation: The non-woven fabric is impregnated. The impregnation time is 1 minute to obtain semi-finished product A. Solidification: The semi-finished product A is put into a solidification tank for 60 minutes of solidification treatment, followed by water washing to remove all the solvents, and then put into an oven for drying. The drying time is 20 minutes and the drying temperature is 150 °C. A polyurethane impregnated structure is formed in the non-woven fabric, and the weight ratio of the polyurethane impregnated structure to the non-woven fabric is 0.8:1 to obtain a polishing pad.
[0039] The fiber specifications of polyester fiber and viscose fiber can be 20 - 50 D / 45 - 60 mm, and both are preferably 30 D / 50 mm in this embodiment; the solvent is DMF. The gram weight of the non-woven fabric is 180 g / m 2 。
[0040] The solidification tank contains a solidifying agent which completely submerges the semi-finished product A, and the solidifying agent is water.
[0041] Example 2 The difference between Example 2 and Example 1 lies in: different process conditions and raw materials, specifically as follows: A polishing pad for polishing a silicon substrate is prepared by the following method: Polyurethane adhesive solution: By weight, 50 parts of polyurethane with an elastic modulus of 40 MPa, 50 parts of polyurethane with an elastic modulus of 65 MPa, and 160 parts of solvent are weighed and mixed evenly to obtain a polyurethane adhesive solution; Non-woven fabric: By weight percentage, 25% polyester fiber and 75% viscose fiber are weighed and mixed evenly, and then transferred to a needling device for needling to obtain a non-woven fabric; Impregnation: The non-woven fabric is impregnated. The impregnation time is 2 minutes to obtain semi-finished product A. Solidification: The semi-finished product A is put into a solidification tank for 50 minutes of solidification treatment, followed by water washing to remove all the solvents, and then put into an oven for drying. The drying time is 15 minutes and the drying temperature is 155 °C. A polyurethane impregnated structure is formed in the non-woven fabric, and the weight ratio of the polyurethane impregnated structure to the non-woven fabric is 0.8:1 to obtain a polishing pad.
[0042] Example 3 The difference between Example 3 and Example 1 lies in: different process conditions and raw materials, specifically as follows: A polishing pad for polishing a silicon substrate is prepared by the following method: Polyurethane adhesive solution: By weight, 60 parts of polyurethane with an elastic modulus of 40 MPa, 40 parts of polyurethane with an elastic modulus of 65 MPa, and 140 parts of solvent are weighed and mixed evenly to obtain a polyurethane adhesive solution; Non-woven fabric: By weight percentage, 35% polyester fiber and 65% viscose fiber were weighed and mixed evenly, and then transferred to a needling device for needling to obtain a non-woven fabric; Impregnation: The non-woven fabric was subjected to impregnation treatment, impregnated for 1 minute to obtain semi-finished product A; Solidification: The semi-finished product A was placed in a coagulation tank for coagulation treatment for 70 minutes, then washed with water to remove all solvents, and placed in an oven for drying. The drying time was 25 minutes and the drying temperature was 145 °C. A polyurethane impregnated structure was formed in the non-woven fabric, and the weight ratio of the polyurethane impregnated structure to the non-woven fabric was 0.8:1 to obtain a polishing pad.
[0043] Example 4 The difference between Example 4 and Example 1 is that it further includes 1 part by weight of the moisture absorption and penetration agent obtained in Preparation Example 1. The polyurethane adhesive solution was obtained by the following method: By weight, 55 parts of polyurethane with an elastic modulus of 40 MPa, 45 parts of polyurethane with an elastic modulus of 65 MPa, 150 parts of solvent, and 1 part of moisture absorption and penetration agent were weighed and mixed evenly to obtain a polyurethane adhesive solution.
[0044] Example 5 The difference between Example 5 and Example 1 is that it further includes 2.8 parts by weight of the moisture absorption and penetration agent obtained in Preparation Example 1.
[0045] Example 6 The difference between Example 6 and Example 1 is that it further includes 3.5 parts by weight of the moisture absorption and penetration agent obtained in Preparation Example 1.
[0046] Example 7 The difference between Example 7 and Example 5 is that the source of the moisture absorption and penetration agent is different, as specifically described in Table 2; Table 2 Sources of moisture absorption and penetration agents in Examples 7 - 12 (%) Examples Source of the moisture absorption and penetration agent Example 7 Preparation Example 2 Example 8 Preparation Example 3 Example 9 Preparation of Comparative Example 1 Example 10 Preparation of Comparative Example 2 Example 11 Preparation of Comparative Example 3 Example 12 Preparation of Comparative Example 4 Comparative example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that 70% polyester fiber and 30% viscose fiber were mixed evenly.
[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the viscose fiber was replaced with polyester fiber.
[0048] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the polyurethane with an elastic modulus of 40 MPa was replaced with an equal amount of polyurethane with an elastic modulus of 65 MPa.
[0049] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the polyurethane with an elastic modulus of 65 MPa is replaced in equal amount by the polyurethane with an elastic modulus of 40 MPa.
[0050] Performance detection test Detection method / Test method The polishing pads obtained in Examples 1 - 12 and Comparative Examples 1 - 4 were used in a polishing equipment. After polishing a silicon wafer, the following evaluations were carried out; 1. Observe whether there are phenomena such as scratching and stains on the surface of the silicon substrate. If any of the above phenomena occur, it is recorded as unqualified, and the product qualification rate is calculated. After the polishing pad is used for 10 hours, the polished silicon substrate is taken out and observed for the surface. The unqualified samples are counted, and the qualification rate is calculated. Similarly, the qualification rate of the samples after being used for 20 hours is tested.
[0051] 2. After polishing, the polishing pad is cleaned and then evaluated. By observation, the corresponding wear degree is obtained. Slight wear: the wear area accounts for 1 - 5%; Moderate wear: the wear area accounts for 6 - 12%; Severe wear: the wear area accounts for 13% and above. The polishing pad is used for 20 hours each time, then put into an ultrasonic cleaner to be cleaned, dried, and then used again in the polishing equipment. Repeatedly like this, when it is used 20 times, observe the wear degree of the surface.
[0052] 3. Refer to ISO 17696 - 2004 for detecting the tear strength of the polishing pads obtained in Examples 1 - 12 and Comparative Examples 1 - 4.
[0053] The above experimental data are specifically shown in Table 3; Table 3 Experimental data of Examples 1 - 12 and Comparative Examples 1 - 4 Combined with Example 1 and Comparative Examples 1 - 4 and Table 1, it can be seen that in Comparative Example 1, serious wear phenomena occurred and the tear strength was relatively large, indicating that wear and other phenomena were likely to occur. The qualification rate of Comparative Example 2 at 10 h was lower than that of Example 1, and after polishing for 20 h, the reduction rate of its qualification rate was relatively large, indicating that it was difficult to adsorb impurities during the polishing process; in Comparative Example 3, the wear was serious, and the qualification rate of Comparative Example 4 was relatively low. It shows that using the non - woven fabric produced from viscose fiber and polyester fiber in the amount ratio of the present application, and then cooperating with the two - modulus polyurethane used in the present application can improve the comprehensive performance, thereby enabling the polishing pad to have better comprehensive performance, obtaining better durability and improving the polishing quality of the silicon substrate.
[0054] Combined with Example 1, Examples 9-12, and Example 4 and with reference to Table 1, it can be seen that after 20 hours of use in Example 1 and Examples 9-12, the qualified rate is lower than that in Example 4, and the tearing strength is also relatively low. This shows that the wetting penetrant prepared from methyl vinyl ether-maleic anhydride copolymer, (acryloxymethyl)dimethylmethoxysilane, maleic anhydride amino alcohol acrylate, carboxyl polycaprolactone, initiator, and active diluent in this application, when used in polyurethane adhesive, can easily penetrate into the interior of the non-woven fabric and form a uniform and stably adhered polyurethane infiltration structure on the fiber surface of the non-woven fabric. At the same time, it can also promote the adsorption of fine impurities generated during the polishing process by the non-woven fabric, ensure the cleanliness of the polished surface, avoid scratching the surface of the silicon substrate, promote the adsorption of impurities and polishing liquid by the non-woven fabric, and keep the polishing pad at a certain degree of infiltration, avoid wearing the silicon substrate during the polishing process, improve the qualified rate after polishing the silicon substrate, and have a longer polishing cycle, reducing the possibility of frequent replacement.
[0055] This specific embodiment is only an explanation of the present application and does not limit the present application. After reading this specification, those skilled in the art can make modifications to this embodiment without creative contributions as needed, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.
Claims
1. A polishing pad for polishing a silicon substrate, comprising a non-woven fabric and a polyurethane dipping structure, wherein the dipping layer is formed by dipping a polyurethane adhesive into the non-woven fabric and curing the non-woven fabric, characterized in that: The non-woven fabric is produced by needle punching process with 25-35wt% polyester fiber and 65-75wt% viscose fiber; the polyurethane glue comprises: 50-60 parts by weight of polyurethane with elastic modulus of 38-45MPa, 40-50 parts by weight of polyurethane with elastic modulus of 60-70MPa, and 140-160 parts by weight of solvent.
2. A polishing pad for polishing a silicon substrate according to claim 1, characterized in that: The solvent is DMF.
3. The polishing pad for polishing a silicon substrate according to claim 1, characterized in that: The fiber specifications of the polyester fiber and the viscose fiber are both 20-50D / 45-60mm.
4. The polishing pad for polishing a silicon substrate according to claim 1, characterized in that: The polyurethane adhesive also includes 1-3.5 parts by weight of a moisture absorbing and penetrating agent.
5. A polishing pad for polishing a silicon substrate according to claim 4, characterized in that: The moisture absorbing penetrant is prepared from the following raw materials in weight percentage: Methyl vinyl ether-maleic anhydride copolymer 10-30% (Acryloxymethyl) dimethylmethoxysilane 5-10% Maleic anhydride amino alcohol acrylate 2-8% Carboxylic polycaprolactone 2-10% Initiator 1-2% The balance is activated diluent.
6. A polishing pad for polishing a silicon substrate according to claim 5, characterized in that: The activated diluent is acrylate-based polyethylene glycol.
7. A polishing pad for polishing a silicon substrate according to claim 5 or 6, characterized in that: The hygroscopic penetrant is prepared by the following method: According to weight percentage, methyl vinyl ether-maleic anhydride copolymer, (acryloxymethyl) dimethylmethoxysilane, maleic anhydride amino alcohol acrylate, carboxyl polycaprolactone, active diluent and initiator are weighed and mixed evenly, and heated for reaction to obtain a moisture absorbing and penetrating agent.
8. A method for preparing a polishing pad for polishing a silicon substrate according to any one of claims 1 to 7, characterized in that: The following steps are involved: Polyurethane glue: According to weight percentage, polyurethane with an elastic modulus of 38-45 MPa, polyurethane with an elastic modulus of 60-70 MPa, and solvent are weighed and mixed evenly to obtain polyurethane glue; Non-woven fabric: According to the weight percentage, polyester fiber and viscose fiber are weighed and mixed evenly, and then sent to the needle punching equipment for needle punching to obtain non-woven fabric; Dipping: dipping the non-woven fabric into glue to obtain a semi-finished product A; Solidification: The semi-finished product A is placed in a solidification tank for solidification treatment, and then washed with water and dried to obtain a polishing pad.
9. The method for preparing a polishing pad for polishing a silicon substrate according to claim 8, characterized in that: The dipping time is 1-2 minutes; the solidification time is 50-70 minutes; the drying time is 15-25 minutes, and the drying temperature is 145-155°C.
10. The method for preparing a polishing pad for polishing a silicon substrate according to claim 8, characterized in that: The polyurethane adhesive solution also includes 0.2-3.5 parts by weight of a moisture absorbing and penetrating agent.